2018
DOI: 10.1177/0363546518802842
|View full text |Cite
|
Sign up to set email alerts
|

Human Subacromial Bursal Cells Display Superior Engraftment Versus Bone Marrow Stromal Cells in Murine Tendon Repair

Abstract: Background: Bone marrow aspirate is a primary source for cell-based therapies with increasing value in the world of orthopaedic surgery, especially in revision cases of tendon and ligament repairs. However, cells within peritendinous structures, such as the paratenon and surrounding bursa, contribute to the native tendon-healing response and offer promising cell populations for cell-based repair strategies. Therefore, the purpose of this study is to investigate the efficacy of cells derived from human subacrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 33 publications
2
61
0
Order By: Relevance
“…Besides, recent studies suggest subacromial bursa to be a potential, easily accessible source for MSCs that can be used for biologic augmentation of rotator cuff repairs, as they fulfil all required characteristics including multilineage differentiation (9-11). Moreover, Dyrna et al found that human SBDCs demonstrated superior tissue engraftment and survival in an animal tendon model when compared to bMSCs (27). The present study found that SBDCs also adhere and proliferate on DBM scaffolds, highlighting their potential as an easily accessible biologic augment in combination with scaffolds to keep the cells at the targeted zone.…”
Section: Discussionsupporting
confidence: 59%
“…Besides, recent studies suggest subacromial bursa to be a potential, easily accessible source for MSCs that can be used for biologic augmentation of rotator cuff repairs, as they fulfil all required characteristics including multilineage differentiation (9-11). Moreover, Dyrna et al found that human SBDCs demonstrated superior tissue engraftment and survival in an animal tendon model when compared to bMSCs (27). The present study found that SBDCs also adhere and proliferate on DBM scaffolds, highlighting their potential as an easily accessible biologic augment in combination with scaffolds to keep the cells at the targeted zone.…”
Section: Discussionsupporting
confidence: 59%
“…Studies have demonstrated that the paratenon may be instrumental in patella tendon healing. 27 , 28 , 29 The authors feel that the subacromial bursa may serve a similar role in rotator cuff regeneration despite being an extrinsic tissue, perhaps accounting for the large presence of CTPs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work by Dyrna et al. 28 has contributed that bursal donated cells may have superior engraftment and survival in healing tendon than cBMA-derived cells. The results of this study further confirm that bursa is capable of forming colony units in culture.…”
Section: Discussionmentioning
confidence: 99%
“…Application of mesenchymal stem cells (MSCs) is one of the promising new options for rotator cuff tear surgery; several articles have shown the positive effects of this augmentation in animal and human studies. [4][5][6][7] All prior studies have used enzymatic digestion with collagenase to isolate MSCs. The current article "Comparison of Preparation Techniques for Isolating Subacromial Bursa-Derived Cells as a Potential Augment for Rotator Cuff Tear" reported by Morikawa, Muench, Baldino, Kia, Johnson, Otto, Pauzenberger, Dyrna, McCarthy, and Mazzocca 8 revealed that a similar number of subacromial bursaederived cells were obtained using a chopping technique to mechanically isolate cells as when using collagenase digestion.…”
Section: See Related Article On Page 80mentioning
confidence: 99%